Effects of Ecohydraulic Bank Stabilization Structures on Bank Stability and Macroinvertebrate Community in Surabaya River - Daru Setyo Rini; Endang Arisoesilaningsih; Donny Harisuseno; Soemarno Soemarno (Indonesian Journal of Environment and Sustainable Development, 2018)
There were 18 accelerated erosion sites identified along 7 km of Surabaya River Fishery Sanctuary Area. A model of ecohydraulic bank stabilization was applied to reduce bank erosion in Surabaya River at Gresik Regency Indonesia. The model is combination of reprofiled and revegetated bank with rock toe reinforcement and  addition of log groynes. Various native plant species were planted and naturally grown to establish multi-strata littoral vegetation structure. This study assessed effects of ecohydraulic bank stabilization on bank morphology, near bank velocity and littoral macroinvertebrate community during September 2014 to August 2016. The study found that rock toe enforcement, log groynes and reprofiled bank slope could stabilized the eroded bank, and littoral vegetation formation reduced near bank velocity at restored sites. There were 31 families of macroinvertebrate found in Surabaya River with high abundance of moderately pollution sensitive taxa Atyidae and pollution tolerant taxa Corixidae, Chironomidae and Tubificidae. The taxa richness, diversity index and abundance of sensitive and moderately sensitive macroinvertebrate group were increased after application of ecohydraulic bank stabilization at restored area. The results shown that ecohydraulic bank stabilization structure provides multi-benefits in improving bank stabilization against erosion and providing new micro-habitats for biotic community.Keywords:  ecohydraulic bank stabilization, macroinvertebrates, riparian restoration